Characteristics and Risk Factors for Pupillary Capture of Intraocular Lens in Congenital Ectopia Lentis. (2nd April 2020) - Jin, Guangming; Lin, Junxiong; Xiao, Bing; Chen, Aiming; Young, Charlotte Aimee; Zheng, Danying
ABSTRACT: Importance : To analyze the characteristics and risk factors for pupillary capture (PC) of the intraocular lens (IOL) in congenital ectopia lentis (CEL) patients. Methods : Data of CEL patients who underwent lens extraction and intraocular implantation from 2013 to 2016 at Zhongshan Ophthalmic Center in China were collected. Best-corrected visual acuity (BCVA), axial length (AL), refractive status, corneal curvature, intraocular pressure (IOP), degree of lens dislocation, presence of strabismus, and methods of IOL fixation were recorded. Postoperative data were collected from the routine one-month postoperative follow-up. Patients with PC of IOL were characterized and risk factors for PC of IOL were analyzed using age-sex adjusted multiple logistic regression analysis. Results : Of the 89 included CEL subjects, 43.8% (39/89) of them suffered from PC after IOL implantation. There was no statistically significant difference in BCVA, AL, refractive status and IOP between the eyes which developed PC versus those which did not. Age-sex multiple logistic regression analysis shows that PC of IOL was associated with a more severe degree of lens dislocation and eyes with strabismus before surgery. Conclusions : Eyes with strabismus and more severe degrees of lens dislocation before surgery are risk factors for PC of IOL. When treating patients that present these risk factors, preoperative communication, and postoperative follow-up should be strengthened. Considering that PC of IOL has little effect on visual acuity, patients with slight PC of IOL can be exempt from surgical intervention.